Microbial Reduction of Natural Fe(III) Minerals; Toward the Sustainable Production of Functional Magnetic Nanoparticles - Joshi, Nimisha; Filip, Jan; Coker, Victoria S.; Sadhukhan, Jhuma; Safarik, Ivo; Bagshaw, Heath; Lloyd, Jonathan R. (Frontiers in Environmental Science, 2018)
The microbial synthesis of biominerals offers a potentially sustainable green solution for the production of a wide range of industrially relevant functional nanomaterials. Metal-reducing bacteria are of particular relevance, as they can enzymatically reduce a wide spectrum of high oxidation state metals and metalloids, forming cell-templated nanomagnets, catalysts, remediation agents and quantum dots. Although these bioprocesses have been shown to be both scalable and tunable (with respect to particle size, reactivity, magnetic properties and light emitting properties), they have yet to be taken up by industry. Here, we show that naturally abundant Fe(III) minerals are appropriate raw materials for the production of magnetic Fe(II)-bearing nanoparticles by the subsurface bacterium Geobacter sulfurreducens, and these bionanomaterials have the potential for remediation applications (here confirmed by the efficient reduction of toxic, mobile Cr(VI) to less toxic and soluble Cr(III)). Detailed molecular-scale characterization of the bioreduced nanominerals, alongside life cycle assessments and life cycle costings, confirm the efficient production of highly reactive and magnetic nanomaterials from waste materials. This adds further weight to the adoption of microbial technologies for sustainable, functional nanomaterials in a circular economy.